Peran Moderasi Kepemilikan Institusional dalam Hubungan antara Tax Avoidance, Intellectual Capital, dan Nilai Perusahaan - Nurhidayah, Hilda; Soerono, Ayu Noorida (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to test and obtain empirical evidence regarding the effect of tax avoidance and intellectual capital disclosure on firm value with institutional ownership as a moderating variable. The population in this study is primary consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The method used is purposive sampling with a total sample of 156 research data. Data processing is carried out using the SPSS 25 application program using multiple linear analysis and moderated regression analysis (MRA). The results of the study indicate that tax avoidance has a significant negative effect on firm value, and intellectual capital disclosure has a significant positive effect on firm value, while institutional ownership is unable to moderate the impact of tax avoidance and intellectual capital disclosure on firm value.